TEKNIK DAN MANAJEMEN PRODUKSI BIBIT BABI DI BANJAR DAUH UMA, DESA PENGOTAN, KABUPATEN BANGLI - SUMARDANI, NLG; PUTRA, IGA ARTA; SUBERATA, IW; SURANJAYA, IG; PUTRA, DK HARYA; YUPARDHI, WS (Buletin Udayana Mengabdi, 2015)
The short course of management of animal husbandry and using Artificial Insemination (AI) on swine was conducted on September 6th 2014 at Dauh Uma Pengotan Village, Regency of Bangli. There were 15 farmers who merged into group as participants of this activity. The aimed of this activity was to increase litter size of swine with AI program in breeding management. The used method of activity was giving counseling about breeding and health management of animal husbandry in breeding farm, AI program, and then practiced inseminate on swine. Based on the process of short course it was concluded that, the response of participants on AI was very enthusiastic in joining the activity. Keywords : animal husbandry, breeding, artificial insemination, litter size, swine.